Public Service Transformation Strategy Through the Digital Platform of Surabaya Library Data Bank (BANPUSBOYO) - Olivia, Gabriela Natali; Wardiyanto, Bintoro; Setijaningrum, Erna (Journal Research of Social Science, Economics, and Management, 2025)
The demand to reconstruct the image and function of public libraries in the digital age has driven the emergence of transformative initiatives. This descriptive qualitative research aims to analyze the implementation of the Surabaya Library Data Bank (BANPUSBOYO) application by the Surabaya City Library and Archives Office as a strategy to change the service paradigm. By focusing on the internal perspective of organizers, this study reveals how digital innovation is constructed, mobilized, and operationalized to go beyond mere instrumental functions and touch the level of paradigmatic change in viewing the relationship between the state and citizens. Data was collected through semi-structured interviews with five key informants, in-depth observations at three service points, as well as analysis of policy documents and performance reports for the 2021-2025 period. The findings of the study show that BANPUSBOYO functions as a boundary object that brings together the logic of conventional bureaucracy with the demands of the digital society. The implementation of this application triggered a philosophical shift from the custodial paradigm to the paradigm of curatorial access to knowledge. However, this transformation faces a tension between innovation ambition and the realities of existing institutional and regulatory capacity. Based on the analysis, the research concludes that the success of the transformation of the public service paradigm depends on the ability to create narrative alignment between digital vision, institutional structure, and regulatory ecosystem. The theoretical implications of this study enrich discussions on public service logic and digital governmentality in the context of developing countries,